Indonesia’s Local Content Curriculum (LCC) Initiative: Decentralization and Perspectives from High School Classrooms in Banten - MICHAEL SEAN YOUNG (Universitas Jambi, Indonesia, 2019)
This study asked how, and in what ways the local content curriculum (LCC) initiative was being implemented in response to decentralization reforms in Banten, Indonesia. A discussion of the background of decentralization and LCC policy and their implementation builds a framework for understanding the development of the LCC. Specific attention is given to school-based teams and curriculum development in relation to Indonesian decentralization policy (macro level) and the LCC as a proxy for the policy at the micro level. The ethnographic case study investigated nine lecturers and 25 students at a university faculty of teacher training and education program, and 16 LCC senior secondary teachers in five high schools. Data were collected through primary interviews, follow- up conversations, and classroom participant-observations. The study was a sustained, ten-month long immersion in the school communities in order to yield data adequate to answer the research questions. The discussion and findings provide extensive and diverse evidence of dynamic responses to LCC policy changes, as lecturers and teachers were well informed about and engaged in the implementation of LCC courses. Implications of findings are discussed.